Political Advertising in South Africa - Brian Pottinger (Communicare)
A CHANGING political culture in South Africa has seen in recent years a massive ex pansion in the use of political advertising - both by extra-parliamentary pressure groups and establishment mainstream parties. Standards of commercial advertising in South Africa are controlled by the Trade Practices Act and editorial copy by the terms of the Media Council's Code of Conduct. Remarkably, political advertising is subject to neither. This article examines the impact of political advertising in three aspects: effects on the political debate itself, the audi alteram partem rule of journalistic balance and the over-all impact on the culture of the newspapers in which the advertisement ap pears. A brief survey of the role of political adver tising in other countries is included as well as some observations on the way in which ma jor foreign newspapers approach political advertising. The author argues against further statutory controls on the content of political advertising but suggests that the newspaper industry itself has a responsibility to counter patently false or tendentious political adver tising in its columns.